Data Circulation in Health Landscapes - Niccolò Tempini; Antonio Maturo; Elisabetta Tola (Tecnoscienza, 2022)
The Crossing Boundaries intends to open a dialogue between Science and Technology Studies, Social Studies of Health and the emerging Data Journalism perspective. It explores major issues at stake in contemporary practices of producing and sharing data, with a focus on the COVID-19 pandemic.